Development of a selective HDAC inhibitor aimed at reactivating the HIV latent reservoir. Issue 17 (1st September 2020) - Clausen, Dane J.; Liu, Jian; Yu, Wensheng; Duffy, Joseph L.; Chung, Christine C.; Myers, Robert W.; Klein, Daniel J.; Fells, James; Holloway, Kate; Wu, Jin; Wu, Guoxin; Howell, Bonnie J.; et al.
Graphical abstract: Abstract: The synthesis and SAR development of a trisubstituted imidazole HDAC inhibitor is described. The compounds were synthesized with high diastereocontrol by leveraging Ellman sulfinyl imine chemistry. Structural elucidation provided insight into binding mode and supported design rational. Pharmacokinetic properties of lead compounds were determined.